GAME TECHNOLOGIES IN THE PROCESS OF MASTERING THEORETICAL MUSICAL DISCIPLINES - Viktorovna Pereverzeva, Marina; Ivanovna Anufrieva, Natalia; Semenovna Avramkova, Irina; Olegovna Kuznetsova, Elena; Iosifovna Shcherbakova, Anna (Revista Inclusiones, 2020)
The purpose of the work is to describe game technologies used in the process of mastering theoretical musical disciplines by students of Russian musical universities and faculties, which are proven the most effective in the course of the study of history and theory of music. The main results of the study state that changing the format of the presentation of information and the preference for interactive forms of teaching and game technologies lead to higher teaching outcomes. The use of game technologies allows modern students to more effectively master theoretical musical disciplines. As representatives of the information society, they experience problems with the development of analytical thinking and learn worse than their predecessors. The novelty of the work is the presentation of the results of the development and practical application of specific game situations, which are proven an effective method of teaching history and theory of music. The main findings of the study: in the conditions of the post-industrial world, the world of total synthesis, globalization, and rapid flow of information, modern people have poorly developed analytical thinking. Game technologies partially solve these problems, allowing students to form competencies that are relevant in modern life.